Lyme Disease An Evidence-based Approach - Halperin, John J (CABI, 2014)
Spirochaetal infections somehow seem to take on larger-than-life roles. ‘The French disease’, a.k.a. syphilis, assumed almost mythic proportions. Initially brought back from the New World to the Old, perhaps as divine retribution for measles, smallpox and myriad other curses visited on North America’s aboriginal populations by European conquerors, neurosyphilis aﬀ ected so many historic personalities as to give it a legitimate claim as a molder of history. Even early in the 20th century, a lack of understanding of the pathophysiology of many other diseases led to the at ribution of all manner of disorders to this infection, ot en by default, because nobody could come up with a bet er explanation. Early in the history of Lyme disease, many latched on to the syphilis parallel, asserting that this new spirochaetosis, like its cousin, could masquerade as innumerable other ailments. However, the greatest similarity between the two has been the tendency to inappropriately at ribute unrelated, but otherwise not readily explained, disorders to the unjustly accused spirochaete. The past decade or two has seen medicine move broadly and strongly towards the requirement for evidence-based support for its conclusions and actions. For those of us over a certain age, although this is certainly intellectually satisfying, it produces a distinct cognitive dissonance. When I was a resident, the truth was what the professors said and wrote in textbooks. The evidence basis at best consisted of case series and anecdotal observations. Unfortunately, even the most brilliant minds, individuals who led medicine for decades, were ot en proved wrong as new technologies – imaging, biochemical assays, DNA analysis or whatever – provided more powerful tools to answer questions.